Circular mRNA-LNP vaccine encoding self-assembled E2-TMD-mi3 nanoparticles licit enhanced CSFV-specific immunity over commercial subunit vaccine - Liu, Chunxi; Zhai, Weifeng; Nie, Wenhao; Zhong, Conghao; Diao, Feifei; Yin, Bo (Frontiers in Immunology, 2025)
The E2 subunit vaccine is crucial for eliminating Classical Swine Fever Virus (CSFV) due to its favorable biosafety and Differentiating Infected from Vaccinated Animals (DIVA) capability. However, low immunogenicity and high costs limit its broader application. To overcome these bottlenecks, we leveraged mRNA-LNP technology to design next-generation E2 glycoprotein vaccines with enhanced immunogenicity and cost-effectiveness. We designed different E2 glycoprotein coding sequences incorporating CD154 adjuvants and mi3 self-assembled nanoparticles, delivered via cmRNA-LNP formulations in murine immunogenicity testing. Among these, E2-TMD-mi3 cmRNA-LNP vaccine induced high-titer antibodies with a 78.25% ± 1.32% blocking rate at day 14 post-booster, significantly higher than the commercial subunit vaccine (39.74% ± 3.30%, p<0.01). To further optimize vaccine performance, we compared cmRNA-LNP formulations incorporating with different cationic lipids. Notably, AX4-LNP formulation induced superior cellular and humoral immunity compared to other cationic lipids. In mice, this vaccine induced robust humoral immunity, achieving a mean blocking rate of 80.55% ± 2.06% by day 14 post-booster, alongside potent cellular immunity (IFN-γ ELISpot, 319.60 ± 45.23 SFC/105 cell, 5.6-fold higher than that of the commercial vaccine). In swine, the CSFV-specific antibody blocking rate remained at 54.76% ± 3.21% at 120 days post-primary vaccination. In contrast, the antibody blocking rates in other cmRNA-LNP vaccine groups and the commercial vaccine group were below the positivity threshold (<40%, set according to the manufacturer’s technical specifications), outperforming commercial subunit vaccines. Moreover, this vaccine does not affect the body weight gain of immunized pigs and does not cause inflammatory reactions at the immunization site. Ultimately, we successfully developed a cmRNA-LNP vaccine incorporating the E2-TMD-Mi3 coding sequence and AX4-LNP, which demonstrated superior immunogenicity compared to commercial subunit vaccines. This study establishes a modular cmRNA-LNP platform combining mi3 nanoparticles, overcoming traditional subunit vaccine limitations for porcine viral pathogens.